Manajemen Risiko Perbankan Syariah: Manajemen Risiko Perbankan Syariah - Dimas Kenn Syahrir; Ickhsanto Wahyudi; Santi Susanti; Darwant Darwant; Ibnu Qizam (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
Nowaday, the development of sharia banking on a global scale is increasing rapidly marked by major advances in muamalah issues due to the emergence of the desire of the majority of Muslims to practice Islam in a comprehensive manner, including in the field of Islamic economics, especially sharia banking. In carrying out its operational activities, sharia banks must implement sharia principles so that a good regulatory framework is needed in order to create a good environment for the growth and development of the sharia banking industry and the stability of the financial sector as a whole. The effectivity of risk management in Islamic banks needs special attention because there are many complex issues that need to be better understood, especially related to the nature of the specific risks faced by Islamic banks simultaneously related to the ways and methods of Islamic financing through the use of a combination of methods and contracts that are permissible related issues regarding returns or PLS (profit loss sharing) and non-PLS so that this paper will raise a number of issues in risk measurement, recognition, collateral adequacy and others. Therefore, this paper aims to discuss various solutions, innovations and appropriate adjustments from the aspect of risk management related to the special characteristics of Islamic financial products and services in Islamic banking.